2009
DOI: 10.1021/pr800937k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Natural MHC Class II Presented Phosphopeptides and Tumor-Derived MHC Class I Phospholigands

Abstract: MHC molecules present protein-derived peptides to T lymphocytes. By developing TiO2-based microcentrifugation columns, we identified the first phosphorylated MHC class I ligands from tumor tissue (renal cell carcinoma) and, by comparison to healthy renal tissue, found one Brf1-derived ligand as potentially tumor-associated. We further discovered the first natural phosphorylated MHC class II ligands. They revealed several novel phosphorylation sites of significant transmembrane receptors, such as Frizzled 6, CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 83 publications
6
52
0
Order By: Relevance
“…S9). Comparison with previous studies revealed that 16 HLA-B7-associated phosphopeptides had been reported previously (16,24,26), whereas a total of 24 phosphorylation sites are annotated in the Uniprot protein database (www.uniprot.org/). The correct identification of selected phosphopeptides could be nicely confirmed by the spectra we generated from their synthetic peptide counterparts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 59%
“…S9). Comparison with previous studies revealed that 16 HLA-B7-associated phosphopeptides had been reported previously (16,24,26), whereas a total of 24 phosphorylation sites are annotated in the Uniprot protein database (www.uniprot.org/). The correct identification of selected phosphopeptides could be nicely confirmed by the spectra we generated from their synthetic peptide counterparts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 59%
“…The identification of phosphorylated species associated with HLA class I molecules has gained considerable attention since they were proposed as putative targets for cancer immunotherapy (12,13). Nevertheless, the identification of phosphopeptides via mass spectrometry is challenging because of several analytical limitations, such as their low stoichiometry, their inefficient ionization, or the poorly informative MS2 spectra obtained upon their fragmentation by collision-induced dissociation (18,19).…”
Section: To Test This Hypothesis the Natural Ligands S[ps]ygnirav Anmentioning
confidence: 99%
“…In the same way, identification of HLA class I-associated phospholigands has benefited from the implementation of these approaches (11)(12)(13). We combined IMAC and TiO 2 affinity chromatography before LC-MS analysis, resulting in the identification of 85 B40-bound phosphopeptides.…”
Section: To Test This Hypothesis the Natural Ligands S[ps]ygnirav Anmentioning
confidence: 99%
See 2 more Smart Citations